Examen especial a la gestión administrativa del Gobierno Autónomo Descentralizado Parroquial de San Carlos, año 2022. - Mendoza Montes, Dayanara Valeria (2024)
The main objective of this research project was to examine the administrative management of the Autonomous Decentralized Parish Government of San Carlos during the year 2022. It focused on verifying compliance with the Annual Operational Plan, determining the level of efficiency in administrative management and pointing out critical points for proper decision making. The analysis identified relevant aspects in the administrative management of the San Carlos Parish Government during the year 2022. Compliance or, failing that, non-compliance with the Annual Operational Plan, which is essential to guide activities and achieve the institution's strategic objectives, was verified. In addition, the level of efficiency in administrative management was evaluated through the application of relevant indicators. This made it possible to measure the performance and optimization of administrative processes, identifying areas for improvement and opportunities for efficiency. Likewise, the critical points found in the administrative management of the GAD Parroquial de San Carlos during the year 2022 were highlighted. These critical points are key elements that require immediate attention and actions to improve decision making and ensure a more effective management.